Estudio de factibilidad para una empresa distribuidora de productos de consumo masivo para la cadena de comedores para la empresa reybanpac, sector fumisa, canton Buena Fe, año 2013. - Olmedo Intriago, Irene Alejandra (2014)
research is based on a feasibility study for the establishment of a distributor of consumer products in Canton Good Faith, is accurate, important and positive the expected information to state that if the development of the proposal is feasible, with real basis of the environment, which aims to develop and meet its targets for implementing the same, so the following salient features defined in the structuring of the project: It is determined that the study has raised foundations for the analysis and implementation. This project focuses on theoretical bases, a number of information sources such as texts and internet, which serves as central to the project base. The shape and working system that counts the distribution of consumer products in Canton Good Faith, is through a series of variables and indicators to primarily determine the weaknesses that have existing stores and commissaries to become a job opportunity. The demand in the domestic market is very diverse, which allows focusing the feasibility of the company to potential customers of the distributor, needs, preferences, payment, purchase frequency and forms, credit terms, profitability, services in the acquisition of products and unmet demand. The feasibility study is able to meet needs, presenting a variety of products and competitive prices, projected based on economic variables - financial market and consumer. It has been designed according to the results that demand for consumer products will increase in the coming years so that you can point to this potential market and not just the set. Competition distributor in Canton Good Faith is very low with what you have resounding success. The project engineering is totally acceptable in terms of availability and investment as these items are expected in this project has been developed to reduce the impact caused the weaknesses identified in the diagnosis, therefore the proposal in question is related with the theme of location, infrastructure, design, mission, vision, strategic objectives, marketing process, investment and financing, running through an economic and financial analysis of the cost benefit in the short term and long term which shows that this research project is viable. Ultimately, impact, positive or negative signs and aspects of project implementation will result in a certain area, whereby it came to drawing the conclusions and recommendations of the research conducted is determined. For the project the investment is of $ 150,000.00 which will be financed through a bank loan granted by Bank Pichincha will need an IRR of 74.63% which means the project's viability was obtained since it exceeds the opportunity cost, plus the NPV of $ 8.468,48 determines that the project has positive balance which is greater than zero which determines that the project is profitable, as the cost benefit per dollar invested will get useful $1, 69 cents future recovery so investment is desirabl